Interspecific hybridization in niger (Guizotia abyssinica l.f. cass): Interspecific hybridization in niger (Guizotia abyssinica l.f. cass) - M SUJATHA; HELAN BABY THOMAS; H D PUSHPA; R PARIMALAN (Journal of Oilseeds Research, 2023)
The study presents the results of successful establishment and interspecific hybridization of cultivated Niger (Guizotia abyssinica) with one of its wild allies, G. scabra. Out of four accessions of wild species collected from Kenya, two accessions (P3: EC1077609 and P4: EC1077610) could be successfully established that were used in interspecific crosses. Direct and reciprocal crosses were made (JNS-28 x P3; JNS-28 x P4) and adequate quantity of F1 seed was obtained in crosses of wild x cultivated. Morphological analysis of the F1 hybrids showed the vigorous nature of the interspecific hybrids and the results are presented.